2015
DOI: 10.1242/jcs.168849
|View full text |Cite
|
Sign up to set email alerts
|

A Brn2–Zic1 axis specifies the neuronal fate of retinoic-acid-treated embryonic stem cells

Abstract: Mouse embryonic stem cells (ESCs) treated with all-trans retinoic acid differentiate into a homogenous population of glutamatergic neurons. Although differentiation is initiated through activation of target genes by the retinoic acid receptors, the downstream transcription factors specifying neuronal fate are less well characterised. Here, we show that the transcription factor Brn2 (also known as Pou3f2) is essential for the neuronal differentiation programme. By integrating results from RNA-seq following Brn2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…Our data confirm original reports on the possibility of generating GABAergic neurons from EC cells 38 , 56 and extend such observations at several levels. First, by applying retinoid treatment during embryoid body formation 35 , we show that the rate of neurogenesis (88%) and homogeneity of obtained GABAergic neurons (90% of neurons) are much higher than previously reported (30–70% for neurogenesis and 60% for GABAergic neuron enrichment) 38 . Accordingly, we observed only rare astrocytes and no microglial cells, in contrast to previous reports, as confirmed by a comparative analysis of cells differentiated through the protocols reported by Staines et al .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Our data confirm original reports on the possibility of generating GABAergic neurons from EC cells 38 , 56 and extend such observations at several levels. First, by applying retinoid treatment during embryoid body formation 35 , we show that the rate of neurogenesis (88%) and homogeneity of obtained GABAergic neurons (90% of neurons) are much higher than previously reported (30–70% for neurogenesis and 60% for GABAergic neuron enrichment) 38 . Accordingly, we observed only rare astrocytes and no microglial cells, in contrast to previous reports, as confirmed by a comparative analysis of cells differentiated through the protocols reported by Staines et al .…”
Section: Discussionmentioning
confidence: 60%
“…To address the role of ATRA in generation of specific neuronal types and subtypes, we used a differentiation protocol applied recently to dissect genetic programs underlying ATRA-induced neurogenesis in EC cells 35 . Differentiation of EC aggregates was induced by ATRA, or selective agonists of RARα (BMS753), RARβ (BMS641), or RARγ (CD666).…”
Section: Resultsmentioning
confidence: 99%
“…3 ), sequence analysis of the NTF3 promoter region ranging from nt − 1390 to nt − 524 also revealed several putative binding sites for some important differentiation-related transcription factors such as CTCF, YY1, GATA-3, and Sp-1 [ 31 ]. In addition, the regulatory role of Zic 1 in neuronal differentiation has been addressed in embryonic mouse models [ 16 ]. We found that POU3F2 knockdown resulted in decreased Zic1 expression in NT2D1 cells with or without neuronal induction (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Forced expression of POU3F2 and other neuronal transcription factors (ASCL1, MYT1L, and NEUROD1) has been shown to induce neuronal fate in pluripotent stem cells and to convert fetal and postnatal human fibroblasts or somatic cells into functional neurons [ 11 15 ]. More recently, Urban and colleagues demonstrated that POU3F2 was essential for retinoic acid-induced neuronal differentiation from mouse embryonic stem cells by regulating a set of target genes via binding to the genomic locus Zic 1 [ 16 ]. These results indicate that POU3F2 is a critical transcription factor in the conversion of embryonic stem cells into neurons and glial cells; however, little is known about the neurogenic genes it regulates.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to Gmnn’s ability to promote neural fate acquisition of ES cells, Zic1 is required for specification of ES cells as neuronal precursor cells in response to retinoic acid37. In mouse models, Zic1 and Zic3 are required together to regulate forebrain development and cooperate in promoting neural progenitor expansion, while inhibiting neuronal differentiation38, while Zic1 also promotes neural precursor formation and maintenance throughout the neural tube39.…”
Section: Discussionmentioning
confidence: 99%